Who Gets to Come In? How Political Engagement Shapes Views on Legal Immigration - Muhammad Hassan Bin Afzal; Foluke Omosun (ZBW – Leibniz Information Centre for Economics, 2025)
This study examines how political engagement shapes public attitudes toward legal immigration in the United States. Using nationally weighted data from the 2024 ANES Pilot Study, we construct a novel Political Engagement Index (PAX) based on five civic actions—discussing politics, online sharing, attending rallies, wearing political symbols, and campaign volunteering. Applying weighted ordered logistic regression models, we find that higher engagement predicts greater support for easing legal immigration, even after adjusting for education, gender, age, partisanship, income, urban residence, and generalized social trust. To capture the substantive effect, we visualize predicted probabilities across levels of engagement. In full-sample models, the likelihood of supporting "a lot harder" immigration drops from 26% to 13% as engagement rises, while support for "a lot easier" increases from 10% to 21%. Subgroup analyses by partisanship show consistent directionality, with notable shifts among Republicans. Social trust and education are also consistently associated with more open attitudes, while older respondents tend to support less easy pathways to legal immigration policies. These findings suggest that a cumulative increase in political participation is associated with support for legal immigration in shaping public attitudes toward legal immigration pathways, with varying intensity across partisan identities and socio-demographic characteristics.
Conference: MPSA 2025 Annual Conference
Keywords: D72; F50; 330; Political Engagement; Immigration Policy; Voting Behavior; Civic Participation; Issue Salience; Elite Cues